Portfolio management and diversification strategies of property companies listed on the Stock Exchange of Singapore. - Heng, Aik Swan. (2009)
Property companies in Singapore are subject to the ups and dowas of the property market and the economy. Within the property market itself, the various sectors - commercial, residential, industrial and hotel - also has their own cyclical patterns. Diversification of the property portfolio is thus important to maximise returns with minimum risks in the faces of these market cycles.